2005
DOI: 10.1038/sj.mp.4001741
|View full text |Cite
|
Sign up to set email alerts
|

Differential protein expression in the prefrontal white matter of human alcoholics: a proteomics study

Abstract: Neuroimaging and post-mortem studies indicate that chronic alcohol use induces global changes in brain morphology, such as cortical and subcortical atrophy. Recent studies have shown that frontal lobe structures are specifically susceptible to alcohol-related brain damage and shrinkage in this area is largely due to a loss of white matter. This may explain the high incidence of cognitive dysfunction observed in alcoholics. Using a proteomics-based approach, changes in protein expression in the dorsolateral pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 60 publications
3
78
0
5
Order By: Relevance
“…46,[48][49][50][51] Such studies have confirmed the differential abundance of certain proteins and provided refined hypotheses regarding the molecular mechanisms of these diseases. Two-dimensional electrophoresis (2DE), which separates protein species by both isoelectric point and molecular weight, 52 has been widely used and recently been improved through the addition of direct labeling of proteins with cyanine (Cy) dyes to facilitate quantitation (two-dimensional difference gel electrophoresis (2D-DIGE)).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…46,[48][49][50][51] Such studies have confirmed the differential abundance of certain proteins and provided refined hypotheses regarding the molecular mechanisms of these diseases. Two-dimensional electrophoresis (2DE), which separates protein species by both isoelectric point and molecular weight, 52 has been widely used and recently been improved through the addition of direct labeling of proteins with cyanine (Cy) dyes to facilitate quantitation (two-dimensional difference gel electrophoresis (2D-DIGE)).…”
Section: Introductionmentioning
confidence: 87%
“…The selection of specific pH range used in the present study for separation of proteins in the first dimension was determined empirically and was based on the pH range that provided optimal resolution of proteins present in the complex mixture in question. Previous studies have utilized broad-range pH strips 46,49,50 as well as more narrow-range pH strips 51,55,56,72 for a range of complex protein samples. For complex protein mixtures, it has been noted that the majority of the protein spots resolved using 3-10 pH strip usually fall between 4 and 7 pH.…”
Section: N Tannu Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Sample preparation and two-dimensional gel electrophoresis (2DE) methodology was according to Alexander-Kaufman et al 23 Briefly, 0.04-0.07 g of crude ACC fresh frozen tissue was placed in Buffer 1 (7 M Urea, 2 M Thiourea, 1% C7bZO, 40 mM Tris). Sample suspensions were sonicated 3 Â 10 s at 40% intensity and centrifuged at 14 000 g for 20 min at 151C.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Proteomics was also used to investigate the effects of alcohol abuse in the dorsolateral PFC, which includes Brodmann area 9, with white (wBA9) (Alexander-Kaufman et al, 2006, 2007a and gray matter (gBA9) (AlexanderKaufman et al, 2007a). The dorsolateral PFC is connected to many brain regions involved in cognitive functions by reciprocal projections and is subject to significant shrinkage in alcoholics, particularly the white matter.…”
Section: Proteomic Studies In Human Post-mortem Brainmentioning
confidence: 99%